Membangun Karakter Peduli Lingkungan melalui Edukasi Pengelolaan Sampah Menjadi Produk Tepat Guna di Panti Asuhan Tunas Bangsa - Meutia Anggraini; Ikhsan Arif; Johannes Leonard Sinaga (Jurnal Kemitraan Masyarakat, 2025)
The problem of waste, especially inorganic waste, is becoming an increasingly serious environmental issue in Indonesia, including in the Tunas Bangsa Orphanage. Lack of awareness and skills in waste management has an impact on environmental pollution and the potential for flooding. This leadership project activity aims to build environmental awareness in the children of the Tunas Bangsa Orphanage through education and training in waste management into appropriate products. The methods used include observation, preparation of tools and materials, implementation of education and practice in making flower pots from used bottles, and evaluation through Focus Group Discussion (FGD) with supervising lecturers, administrators and children of the Tunas Bangsa Orphanage. The results of the activity show that this leadership project not only increases the knowledge and skills of children in managing waste, but also fosters awareness and concern for the environment. In addition, this activity encourages the creativity and independence of the children of the orphanage. However, the evaluation also shows that it is necessary to extend the duration and sustainability of the program so that the benefits obtained can be more optimal. Overall, this leadership project is relevant as an educational and solution-oriented effort in overcoming the problem of waste and building environmental awareness from an early age.